Threat Analysis of Nipah Virus as a New Pandemic from the Perspective of Medical Intelligence - Firdaus Sirait; Armi Susandi; Budiman Bela (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
According to World Health Organization (WHO), Nipah virus is a type of infectious disease from 10 types of infectious diseases that can pose a risk to the public health. Besides, it has the potential to become a new pandemic. The State Intelligence Agency has the authority, mandate, and responsibility to actively engage in early detection of a disease that could potentially become an epidemic and cause a threat to national security and interests. The formulation of this research problem is " Threat Analysis of Nipah Virus as a New Pandemic from the Perspective of a Medical Intelligence." The authors used a qualitative descriptive method approach through interviews and literature studies related to Nipah virus research. The results of the research indicated that the Nipah virus has the potential to become a new pandemic that can threaten the Indonesian people health and even the world. Thus, early detection of the Nipah virus spreading in Indonesia is necessary, by collaborating across ministries in implementing preventive measures using a one health concept approach.